2006
DOI: 10.1063/1.2217107
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electroluminescence from silicon p-i-n light-emitting diodes

Abstract: The temperature dependence of electroluminescence from silicon p-i-n light-emitting diodes with a layer of ␤-FeSi 2 particles inserted in intrinsic silicon was investigated. Anomalous blueshift of the peak energy and enhanced electroluminescence intensity of the silicon band-edge emission were observed at temperatures from 50 to 200 K. The electroluminescence intensity was enhanced due to longer diffusion paths of the injected electrons at elevated temperature, as well as thermal escape of the electrons from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…1, and the EL shift scope is coincident with that of the QDs' PL, indicating that the electrically pumped emission comes from the radiative recombination of excitons in QDs, 7 and the temperaturerelated EL redshift is due to thermal lattice expansion also. 4, the EL boosting may be because the electron injection 11 or the hole seizing 22 in QDs is thermally enhanced. Figure 3 shows the EL spectrum versus the applied voltage at the temperature of 197 K. The dependence of the EL intensity on the applied voltage is approximately exponential.…”
Section: Voltage-dependent Electroluminescence From Colloidal Cdse/ Zmentioning
confidence: 99%
“…1, and the EL shift scope is coincident with that of the QDs' PL, indicating that the electrically pumped emission comes from the radiative recombination of excitons in QDs, 7 and the temperaturerelated EL redshift is due to thermal lattice expansion also. 4, the EL boosting may be because the electron injection 11 or the hole seizing 22 in QDs is thermally enhanced. Figure 3 shows the EL spectrum versus the applied voltage at the temperature of 197 K. The dependence of the EL intensity on the applied voltage is approximately exponential.…”
Section: Voltage-dependent Electroluminescence From Colloidal Cdse/ Zmentioning
confidence: 99%
“…In 1997, the first report of electroluminescence (EL) using b-FeSi 2 precipitates as an active layer in a Si p-n diode was presented [1]. Since then, there have been several reports on 1.6 mm EL at room temperature (RT) from b-FeSi 2 particles embedded in Si p-n diodes formed on Si(0 0 1) [2][3][4][5][6][7][8][9]. A b-FeSi 2 epitaxial film grown on Si(0 0 1) exhibits a strong tendency to form islands, due to lattice mismatch between the two materials, when annealed at a high temperature to improve the crystalline quality [10].…”
Section: Introductionmentioning
confidence: 98%
“…Studies on silicon light emission have been reported that propose various methods such as, for example, a method in which silicon is doped with erbium, ion, a method in which β‐FeSi 2 particles are inserted into the I layer in the silicon PIN junction, and visible light emission using organic semiconductors with Si quantum dots . If we consider fusion with the silicon waveguide from the perspective of silicon photonics, the following are required: A silicon optical emitter An emission wavelength in the silicon transparent range Current injection operations A self‐sustaining light source Room temperature operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the silicon light emitting source is the most important element when forming silicon photonics and, as such, silicon, which is an indirect transition-type semiconductor, has to go through phonon transition which results in a drastic decrease in light emission efficiency, which is a problem. 3 Studies on silicon light emission have been reported that propose various methods such as, for example, a method in which silicon is doped with erbium, ion, 4 a method in which -FeSi 2 particles are inserted into the I layer in the silicon PIN junction, 5 and visible light emission using organic semiconductors with Si quantum dots. [6][7][8] If we consider fusion with the silicon waveguide from the perspective of silicon photonics, the following are required:…”
Section: Introductionmentioning
confidence: 99%